UMPSA community engages in collective effort to prepare iftar meals throughout Ramadan - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
GAMBANG, 12 March 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) maintains the concept of cooking according to a schedule for the preparation of iftar meals held collectively according to each department or faculty.